PERKEMBANGAN RISET AI GENERATIF DALAM PEMBELAJARAN PAI DI SMA: STUDI BIBLIOMETRIK BERBASIS VOSVIEWER TAHUN 2022–2025 - Arrafiq, Ahmad; Hidayat, Dzaky; Andika; Syaputri, Zelda; Mahfuza, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of generative Artificial Intelligence (AI) has significantly influenced Islamic Religious Education (PAI) learning at the senior high school level. Technologies based on large language models provide students with fast and interactive access to learning materials, yet they also raise challenges regarding the validity of Islamic content, academic ethics, and digital literacy. This study aims to map research developments on generative AI in PAI learning from 2022 to 2025 using a bibliometric approach. Data were collected from Google Scholar through Publish or Perish, resulting in 100 qualified articles analyzed with VOSviewer through network, overlay, and density visualizations. The findings indicate a significant increase in publication trends, peaking in 2024, reflecting the growing integration of AI within Islamic education research. The co-occurrence analysis identifies three main clusters: technology, user competence, and ethics-innovation. These clusters illustrate that the use of generative AI in PAI learning requires not only technological readiness but also digital literacy and ethical regulation to ensure the validity and integrity of Islamic educational content. This study concludes that generative AI offers substantial potential to enhance PAI learning effectiveness, but it must be accompanied by adequate supervision and strong digital literacy.